Efficient and precise engineering of a 200 kb b-globin human/bacterial artificial chromosome in E. coli DH10B using an inducible homologous recombination system - Narayanan, Kulathuramaiyer; Williamson, R.; Zhang, Y.; Stewart, AF; Ioannou, PA (Stockton Press, 1999)
Gene therapy studies require techniques that allow alter- adapted an inducible homologous recombination system ation of human genomic DNA sequences. Bacterial arti- for use in E. coli DH10B cells, the host strain for BACs ficial chromosome cloning systems (BACs/PACs) bridge and PACs. Using this system, we have introduced PCR the gap between vectors with small inserts and yeast arti- fragments carrying a selectable marker and a reporter ficial chromosomes (YACs). We report the use of a second gene downstream of the IVS I-110 splicing mutation into a generation BAC vector, pEBAC, containing eukaryotic sel- specific site within the b-globin gene sequence. The use ectable markers and combining some of the best features of this inducible system minimises the risk of unwanted of the BAC, PAC and HAEC systems, into which a 185 kb rearrangements by recombination between repetitive sequence containing the human b-globin gene cluster was elements and allows the introduction of relevant modifiretrofitted. To permit the introduction of mutations corre- cations or reporters at any specific sequence within sponding to those causing human pathology, we have BACs/PACs in E. coli DH10B cells.